Digital Transformation Integration & API Management Framework - Pinto, João Pedro Gomes (2022)
Digital transformation is revolutionizing the way organizations reuse legacy systems and connect them with the ever-increasing number of enterprise applications. These applications are usually hosted in the cloud with the legacy and other systems in the companies’ own data centers. This means that hybrid integration architectures are becoming a crucial part of the day-to-day processes inside organizations. The problem with different platforms is that it produces challenges. The same data is spread across different data structures, with different names and formats. This dissertation, devised with Deloitte, aims to design and implement a hybrid integration framework that connects and reuses the legacy systems with the cloud enterprise applications seamlessly to utilize the same data across all systems. Firstly, the existing integration platforms and integration software that could support the development of the API framework will be presented and described. A set of architectural patterns will be presented and described with their respective advantages and disadvantages and the way they fit in the API framework that will be created. The solution will then be evaluated with the Quantitative Evaluation Framework as well as by using system testing to see if the developed solution has quality.